Consolidation of reward memory during sleep does not require dopaminergic activation - Alizadeh Asfestani, Marjan; Brechtmann, Valentin; Santiago, João C. P.; Peter, Andreas; Born, Jan; Feld, Gordon Benedikt (Journal of cognitive neuroscience, 2020)
Sleep enhances memories, especially if they are related to future rewards. Although dopamine has been shown to be a key determinant during reward learning, the role of dopaminergic neurotransmission for amplifying reward-related memories during sleep remains unclear. In this study, we scrutinize the idea that dopamine is needed for the preferential consolidation of rewarded information. We impaired dopaminergic neurotransmission, thereby aiming to wipe out preferential sleep-dependent consolidation of high- over low-rewarded memories during sleep. Following a double-blind, balanced, crossover design, 17 young healthy men received the dopamine d2-like receptor blocker sulpiride (800 mg) or placebo, after learning a motivated learning task. The task required participants to memorize 80 highly and 80 lowly rewarded pictures. Half of them were presented for a short (750 msec) and a long (1500 msec) duration, respectively, which permitted dissociation of the effects of reward on sleep-associated consolidation from those of mere encoding depth. Retrieval was tested after a retention interval of approximately 22 hr that included 8 hr of nocturnal sleep. As expected, at retrieval, highly rewarded memories were remembered better than lowly rewarded memories, under placebo. However, there was no evidence for an effect of reducing dopaminergic neurotransmission with sulpiride during sleep on this differential retention of rewarded information. This result indicates that dopaminergic activation likely is not required for the preferential consolidation of reward-associated memory. Rather, it appears that dopaminergic activation only tags such memories at encoding for intensified reprocessing during sleep.
Gesehen am 19.01.2026